The Role of Women in Education in Feminism Study - M. Saiful Bahri; Fahrurrozi Dahlan; Faizah Faizah; Moh. Fakhri; Nazar Ma'amy (Edumaspul: Jurnal Pendidikan, 2022)
This research aims to find out the role of women in Education. This research uses a qualitative approach. This type of research uses a type of case study research. A case study is a study of "one system." Several techniques are needed to obtain valid data validity, including triangulation, peer examination, and reference completeness techniques. Data analysis in this study was carried out in 3 stages, the first of which was data reduction. The result of this study is that the role of women in the world of Education, especially in schools, is as follows: (1) The role of women in giving advice, namely the advice given by the teacher is direct (provided that the error is minor); (2) The role of women in positive events, namely providing moral education, then academic education to their students; (3) The role of women in setting an example, namely setting an example; and (4) The role of women in giving gifts and punishments, namely giving gifts as a reward for student achievement and giving educational and Islamic punishments. The positive impact on students there is an effort to educate a generation that is righteous, knowledgeable, noble, and skilled. In addition, their presence there also opened up the public's view that women do not always have to work in the domestic field (inside the home), but they can also work outside the home as if they are studying and outside the home. Able to provide a significant role that is not inferior to male society.